Pokazateli sniženija massy tela u junych sportsmenov kiokusinkaj k sorevnovanijam vysokogo urovnja - Bely, K. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
Based on a survey (questionnaire) of participants in the largest All-Russian youth kyokushin competitions among fighters 12-17 years old held as part of the All-Russian Youth Games of the Russian Martial Arts Union in 2019, some specific quantitative characteristics of weight loss by young athletes for competitions were obtained and analyzed. Scientific research on this component of training young athletes in Kyokushin has never been done before. However, for kyokushin as a form of contact martial arts, the problem of weight loss for competitions is very relevant. To solve it, it is necessary to have basic quantitative indicators of the values of weight loss by athletes for the selection of methods for weight loss and subsequent restoration of performance. The aim of the work was to determine specific quantitative indicators of weight loss by athletes 12-17 years old, such as the number and proportion of athletes who reduced weight to the tournament, the absolute value and proportion of weight loss by athletes, the dependence of these characteristics on the gender of athletes. As a result of the work, it was concluded that, in Kyokushin, the practice of weight loss in young athletes is currently less common than in some other martial arts, and weight loss is associated not with moving to another category, but more with weight correction.Weight loss in Kyokushin is an essential but underutilized reserve for preparing athletes for competition.